The methods of ethics - Crisp, R (Firenze University Press, 2018)
The paper begins with an account of the intellectual background to Henry Sidgwick's writing of his Methods of Ethics and an analysis of what Sidgwick meant by a 'method'. His broad distinction between three main ethical theories - egoism, consequentialism, and deontology - is elucidated and accepted. Sidgwick's different forms of intuitionism are explained, as are his criteria for testing the 'certainty' of a potentially self-evident belief. Section 3 discusses dogmatic intuitionism (common-sense morality systematized) and Sidgwick's own view, in the light of his requirement for precision in ethics. The final section concerns the implications of Sidgwick's position on disagreement for ethical theory. It is suggested that we have some knowledge in ethics, on which most converge, but not much. The paper concludes with a recommendation for a more eirenic and less dogmatic approach to philosophical ethics.